EFFECT OF MACROECONOMIC VARIABLES ON THE TELECOMMUNICATION SECTOR SHARE RETURN - Djamaluddin, Said; Gani Hosea, Jefta (Dinasti International Journal of Economics, Finance & Accounting, 2021)
This study aims to see the effect of macroeconomic factors on stock returns in telecommunications companies listed on the Indonesia Stock Exchange for the period 2015 to 2020. The factors analyzed in this study are GDP, inflation, interest rates, and the rupiah exchange rate as independent variables and stock returns. as the dependent variable. The data analyzed in this study belong to the type of quantitative research. By selecting samples using purposive sampling obtained as many as 4 samples of telecommunications companies. The method of analysis of this study uses panel data regression and the data used in this study are secondary data. The results of this study indicate that the coefficient of determination (R2) is 26.32%, while the remaining 73.68% is the fact by other factors outside the study. The results of this study indicate that the GDP variable does no effect on telecommunications stock returns. However, the Inflation and Exchange Rate variables have a significant effect on stock returns with a negative effect. Meanwhile, the interest rate variable has a significant effect on stock returns with a positive effect on stock returns of telecommunications companies listed on the Indonesia Stock Exchange for the 2015-2020 period.